2021
DOI: 10.1007/s00401-021-02279-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of neuronal Rhes as a novel hallmark of tauopathies

Abstract: The farnesyltransferase inhibitor, Lonafarnib, reduces tau inclusions and associated atrophy in familial tauopathy models through activation of autophagy, mediated by the inhibition of farnesylation of the Ras GTPase, Rhes. While hinting at a role of Rhes in tau aggregation, it is unclear how translatable these results are for sporadic forms of tauopathy. We examined histological slides of allocortex and neocortex from multiple postmortem cases in five different tauopathies, FTLD-TDP, and healthy controls usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…An interesting possibility is that Rhes may increase the transmission of prion-like mHTT in vivo via the TNT-like processes. Recent work has shown that tau pathology and spreading can occur via TNTs, and Rhes is a critical determinant of tau pathology (22,23,93,95,96). Remarkably, the spread of tau pathology can occur from the striatum, and tau is also associated with HD pathology (97)(98)(99)(100)(101).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting possibility is that Rhes may increase the transmission of prion-like mHTT in vivo via the TNT-like processes. Recent work has shown that tau pathology and spreading can occur via TNTs, and Rhes is a critical determinant of tau pathology (22,23,93,95,96). Remarkably, the spread of tau pathology can occur from the striatum, and tau is also associated with HD pathology (97)(98)(99)(100)(101).…”
Section: Discussionmentioning
confidence: 99%
“…Rhes interacts with mammalian target of rapamycin (mTOR) kinase and promotes L-DOPA-induced dyskinesia in Parkinson disease (20,21). Apart from its role in striatal diseases, Rhes is also linked to tau pathology, and its mislocalization in human neurons is considered a hallmark of tauopathies (22,23). These results indicate that Rhes orchestrates neuronal abnormalities associated with neurodegenerative diseases, but the precise mechanisms of its action remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Rhes deletion ameliorates, and Rhes overexpression worsens, the HD phenotype in HD cell models (primary neurons, mouse cells, and human embryonic stem cell-derived medium spiny neurons [MSNs]) and HD mouse models ( 25 , 26 ). Recently, Rhes has been linked to tau-mediated pathology involving SUMOylation, and Rhes alterations are now identified as a novel hallmark of tauopathies ( 27 , 28 ). Thus, Rhes–SUMO signaling pathways participate in neurodegenerative disease processes by modulating disease-relevant proteins.…”
mentioning
confidence: 99%
“…Similarly, in the human brain, Rhes transcript was observed in the hippocampal dentate gyrus and in the pyramidal cell layer of CA1, CA2 and CA3 fields [ 10 ], as well as in frontal cortical areas (layers II–VI), with the highest expression observed in layer V of the cerebral cortex [ 16 ]. More detailed studies, somehow supporting and extending such findings, were recently performed by Ehrenberg and colleagues, who documented that, using multiplex immunofluorescence and single nucleus RNA-sequencing approaches in human brain, Rhes is widespread in cortical neurons, CA1 pyramidal neurons, superior frontal gyrus and entorhinal cortex, where it presents an almost total diffuse cytoplasmic distribution [ 6 ]. Nonetheless, additional studies are required to assess Rhes expression in the human midbrain at the level of the SNc.…”
Section: Discovery Of Rhesmentioning
confidence: 77%
“…Together with Dexras1, Rhes differs from other cognate members for having peculiar N- and C-terminal domains [ 3 , 4 ]. In this respect, while the N-terminal sequence, encompassing 1–18 amino acids, is likely to have the binding motif for the deubiquitinating enzyme, the C-terminal cationic domain interacts with Gβ 1 , Gβ 2 and Gβ 3 subunits of heterotrimeric G proteins [ 5 ], and contains a well-conserved CAAX motif that, following the enzymatic post-translational modification (farnesylation), is able to translocate this small protein to the plasma membrane [ 6 , 7 , 8 ].…”
Section: Discovery Of Rhesmentioning
confidence: 99%